Pengaruh Story-Reading (Buku Bilingual) terhadap Perkembangan Kecerdasan Linguistik Anak Usia Dini - Imaratul Ulwiyah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
This study aims to find the effect of story reading on the development of early childhood linguistic intelligence, especially in Al Hikmah Rambipuji-Jember Kindergarten. This type of research is descriptive qualitative. Data collection is done by interview, observation and documentation. From the results of the study it was found that story-reading provides several positive influences on improving linguistic intelligence, namely: (1) early childhood know and understand new vocabulary (2) understand the plot of a story (3) compose words to express an implied message of an story. Conclusion, that story-reading can give effect to the development of early childhood linguistic intelligence. Keywords: Story-Reading, Linguistics, Early Childhood.